TINJAUAN POAC BERKAITAN FINANCIAL TECHNOLOGY (FINTECH) DAN INOVASI KOPERASI INDONESIA - Samari, Samari; Sumantri, Bambang Agus (Universitas Nusantara PGRI Kediri, 2020)
The phenomenon of cooperatives in Indonesia As of December 2017, as many as 40,013 cooperative units were disbanded. Where 7,235 cooperatives were dissolved by the Region and 32,778 were dissolved by the Ministry of Cooperatives and SMEs. However, under the same conditions, the existence of Financial Technology (Fintech) has a role and function so that cooperative management can be done digitally and controlled, as well as member services that can be even better. The research method used a qualitative approach, using literature review. The literature review in question is to analyze the relationship patterns and forms of the POAC management life cycle in the context of fintech and innovation of Indonesian cooperatives. The research subjects were Indonesian cooperatives that existed until December 2017. The object of research was the product management life cycle. Data collection comes from secondary sources (websites, books, other documents) that are relevant according to the study of this research. The results of research on the Financial Technology (Fintech) review of the types of Indonesian cooperative activities are: Financial Technology (Fintech) can be classified into two types of Indonesian cooperative activities, namely goods and services. The cooperative product management innovation life cycle is in the introductory (initial) cycle.